Expression of Cpgp40/15 in Toxoplasma gondii: a Surrogate System for the Study of Cryptosporidium Glycoprotein Antigens - O'Connor, R. M. (American Society for Microbiology, 2003)
Cryptosporidium parvum is a waterborne enteric coccidian that causes diarrheal disease in a wide range of hosts. Development of successful therapies is hampered by the inability to culture the parasite and the lack of a transfection system for genetic manipulation. The glycoprotein products of the Cpgp40/15 gene, gp40 and gp15, are involved in C. parvum sporozoite attachment to and invasion of host cells and, as such, may be good targets for anticryptosporidial therapies. However, the function of these antigens appears to be dependent on the presence of multiple O-linked α-N-acetylgalactosamine (α-GalNAc) determinants. A eukaryotic expression system that would produce proteins bearing glycosylation patterns similar to those found on the native C. parvum glycoproteins would greatly facilitate the molecular and functional characterization of these antigens. As a unique approach to this problem, the Cpgp40/15 gene was transiently expressed in Toxoplasma gondii, and the expressed recombinant glycoproteins were characterized. Antisera to gp40 and gp15 reacted with the surface membranes of tachyzoites expressing the Cpgp40/15 construct, and this reactivity colocalized with that of antiserum to the T. gondii surface protein SAG1. Surface membrane localization was dependent on the presence of the glycophosphatidylinositol anchor attachment site present in the gp15 coding sequence. The presence of terminal O-linked α-GalNAc determinants on the T. gondii recombinant gp40 was confirmed by reactivity with Helix pomatia lectin and the monoclonal antibody 4E9, which recognizes α-GalNAc residues, and digestion with α-N-acetylgalactosaminidase. In addition to appropriate localization and glycosylation, T. gondii apparently processes the gp40/15 precursor into the gp40 and gp15 component glycopolypeptides, albeit inefficiently. These results suggest that a surrogate system using T. gondii for the study of Cryptosporidium biology may be useful.